Variation in Composition of Storage Proteins, Minor Proteins and Amino Acids Across Faba Bean Cultivars - Xiao, T; Roland, IS; Nielsen, SDH; Le, TT; Olesen, E; Larsen, LB; Poulsen, NA (Elsevier BV, 2025)
This study aimed to investigate variations in protein profiles and amino acid (AA) compositions in faba bean seeds among 10 different cultivars. The compositions of salt-soluble proteins and AA were identified and quantified by label-free nano LC-MS/MS and LC-MS/MS (Triple Quadrupole), respectively. The protein contents (dry basis) in faba bean seeds were measured using the DUMAS method, ranging from 21.6 % to 26.8 %. By nano LC-MS/MS, 103 unique proteins were identified under point mutation monitoring analysis and of these, 61 proteins were quantified by label-free quantification. In all cultivars, vicilin and legumin were the most abundant proteins, respectively, varying from 16 to 39 % and 12 to 34 % of total protein content (ⱳ/w). The relative abundance of minor proteins like Bowman-Birk proteinase inhibitors was quantified to constitute around 1 % of the total protein content (ⱳ/w). There were 400 mg essential amino acids (EAAs) detected per gram protein, where histidine showed the highest concentration (64–82 mg/g protein) in all faba beans.
Keywords: Amino acids; Faba bean; Globulin; Legumin; Proteomics; Vicilin; 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences; Vicia faba; Amino Acids; Plant Proteins; Seeds; Tandem Mass Spectrometry; Seed Storage Proteins; Vicia faba; Amino Acids; Plant Proteins; Seeds; Tandem Mass Spectrometry; Seed Storage Proteins